Further Evolution of a New Nonbiological Transcatheter Valvular Prosthesis - Schröter, Filip; Hartrumpf, Martin; Kuehnel, Ralf-Uwe; Ostovar, Roya; Albes, Johannes M. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Polymeric heart valves are constructed from flexible synthetic materials, therefore aiming to combine the advantageous hemodynamic of biological and the longevity of mechanical valve prostheses. One such valve prototype in development is the PIZZA valve constructed of flexible triangular silicone leaflets on a foldable metal base for perspective transcatheter implantation. Here we present further improvements in its performance through structural modifications.Methods Structurally modified prototypes were constructed from silicone sheets and stainless-steel wires. Their performance was then tested in a hemodynamic testing device of the type HKP 2.0.Results Shift from a planar to a cone shape as well as overlapping of the leaflets significantly improved the valves performance, reducing regurgitation as well as systolic pressure gradients.Conclusions The results of the modified prototypes expressed superior performance and represented a step forward on the road to an easily producible, polymeric transcatheter valvular prosthesis.
Keywords: heart valve surgery; aortic valve and root; heart valve; transapical; percutaneous (TAVI)